Towards a smart energy network: The roles of fuel/electrolysis cells and technological perspectives. (8th June 2015) - Zhang, Xiongwen; Chan, Siew Hwa; Ho, Hiang Kwee; Tan, Siew-Chong; Li, Mengyu; Li, Guojun; Li, Jun; Feng, Zhenping
Abstract The current carbon-based energy system is undergoing a profound change driven by the increased concerns over the longevity and security of energy supply, as well as energy-related emissions of carbon dioxide and air pollutions. The evolutionary trend of this transition is toward a smart energy network of the future that is characterized by widespread deployment of clean energy technologies and intelligent energy management technologies. In this transition, hydrogen and fuel/electrolysis cell technologies have crucial roles to play in developing the smart energy network, which is particularly captured in this work. The features of the future energy system, i.e., the smart energy network, are illustrated. In particular, the visions from technical aspects for the deployment of battery-based electric vehicles and fuel-cell-based electric vehicles are discussed. The key technologies and its current status for the smart energy network are reviewed.